Democracy or Oligarchy? Unequal Representation of Income Groups in European Institutions - Lefkofridi, Zoe (2020)
In this study we examine the representation of income groups in two EU-level institutions, the Council and the European Parliament. We find that the political positions of these institutions, and especially of the Council, are always on the right compared to European citizens, though closer to the wealthy among them. However, a more systematic analysis of congruence between different income groups and the Council reveals that while the poor are systematically underrepresented, the rich are not systematically over-represented. This holds both when we examine the poor and the rich across the EU as a whole and when we cluster them according to their respective member states.